2012
DOI: 10.1590/s0066-782x2012005000057
|View full text |Cite
|
Sign up to set email alerts
|

Intervenção Coronariana Percutânea prévia como fator de risco para Revascularização Miocárdica

Abstract: Background: Percutaneous coronary intervention (PCI) has increased as the initial revascularization strategy in chronic coronary artery disease. Consequently, more patients undergoing coronary artery bypass grafting (CABG) have history of coronary stent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 42 publications
1
8
2
1
Order By: Relevance
“…Mortality was 8% in our study, which was similar to many series such as Luiz and associates who had 9.3% mortality 15 , Yu-Ting, and coworkers who had 8.2% mortality 13 and Sandra and coworkers who had 9% mortality. 14 Our patients had 38% ISR, which is in agreement with the study carried out by Sohrab and collaborators, 12 who had 28% ISR.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Mortality was 8% in our study, which was similar to many series such as Luiz and associates who had 9.3% mortality 15 , Yu-Ting, and coworkers who had 8.2% mortality 13 and Sandra and coworkers who had 9% mortality. 14 Our patients had 38% ISR, which is in agreement with the study carried out by Sohrab and collaborators, 12 who had 28% ISR.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the cardiopulmonary bypass time was 102.66±25.34 minutes, and aortic cross-clamp time was 61.82±20.89 min. A longer time was consumed in our patients compared to other series, [14][15] which could be attributed to the more dissection, severe distal coronary arteries disease, and the use of coronary artery patch.…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, patient-reported previous stent use in the first moment was none in the first period and 5.8% in the second moment [ 18 ] . Regarding the 1099 patients who underwent CABG surgery at the Instituto do Coração (Heart Institute) in São Paulo between May 2007 and June 2009, 14.6%had undergone previous coronary angioplast [ 19 ] . Coronary angiography showed that 77.3% of the patients had severe obstructive lesions in 2 or 3 arteries, a proportion that was practically identical to that reported in a recent study conducted in southern Brazil [ 20 ] .…”
Section: Discussionmentioning
confidence: 99%
“…So cardiac surgeons are faced to a new concept; coronary artery bypass grafting (CABG) to stented coronary vessels. Patients undergoing CABG, with the previously stented coronary vessels have higher morbidity and mortality rates [2]. Besides, during CABG, open coronary artery stent-is a dilemma and controversy exists for intervention.…”
Section: Introductionmentioning
confidence: 99%